The clinical and morphological features and prognosis in rare breast carcinomas - I. V. Vysotskaya; G. V. Martynova; V. P. Letyagin; V. D. Ermilova; E. M. Pogodina; E. A. Kim; K. V. Maksimov (ABV-press, 2014)
The paper is based on the retrospective analysis of 1033 history records of the patients treated for diagnosed tubular, mucous, papil- lary, medullary, or metaplastic carcinomas in the clinics of the N.N. Blokhin Russian Cancer Research Center, Russian Academy of Medical Sciences, in 1985 to 2005. After primary therapy, the maximum overall survival in patients with tubular, mucous, or papil- lary carcinoma was 5 years in 90% of the patients and 10 years or more in 85%. That in patients with metaplastic carcinoma was 5 years only in 65% and 10 years or more in less than 50%. Moreover, a negative status in terms of steroid hormone receptors was detect- ed most frequently in this form of carcinoma (p < 0.05) and HER-2/neu hyperexpression in 20% of cases (p < 0.002). Any radical surgical intervention for all rare breast carcinomas assures that more than 80% will survive 10 years and, if not any, will only 60% of the patients (p < 0.001).